PENGARUH BRAND AMBASSADOR DAN BRAND IMAGE TERHADAP KEPUTUSAN PEMBELIAN PADA E-COMMERCE TOKOPEDIA - Novianti, Kamila Fauzia; Lestari, Fitri (Banking & Management Review, 2021)
This study aims to determine the influence of brand ambassadors and brand image on purchasing decisions on e-commerce Tokopedia. The research method used is descriptive and verification methods. The data used are secondary data with data collection techniques through literature study and primary data with data collection techniques using questionnaires with 100 respondents. The sampling method used is the probability sampling technique. The design of hypothesis testing uses multiple linear regression analysis, correlation coefficient, coefficient of determination, t-test, and F test. The results show that partially brand ambassadors do not affect purchasing decisions. Meanwhile, brand image affects purchasing decisions. Simultaneously, the variable brand ambassador and brand image have an effect on purchasing decisions, with a correlation coefficient of 0.838, which is a very strong relationship, while for the coefficient of determination of 70.2%, meanwhile, the coefficient of determination of 70.2% has an effect between brand ambassador and brand image on purchasing decisions, the remaining 29.8% is influenced by other factors not examined.